Acoustic Indices Reveal Fundamental Differences in Daily Phenology of Tropical and Temperate Forest Soundscapes - Laura M. Berman; Santiago Perea; H. S. Sathya Chandra Sagar; Maia Persche; Grace Ingram; Tatiana Maeda; Natalie Yoh; Jorg Müller; Jens Schlüter; Nicolas Zapata; Ciara Wirth; Gonzalo Rivas‐Torres; et al. (Global Ecology and Biogeography, 2026)
Aim Forests support the majority of the planet's terrestrial biodiversity, and in recent years the characterisation of soundscapes has emerged as a powerful tool for understanding forest ecosystems, both in terms of ecology and for the purpose of conservation. But it is still poorly understood to what extent generalisations can be made about soundscapes in different parts of the world, and to what extent we should expect soundscapes to differ regionally. Here, we characterise the dominant acoustic features of forest soundscapes on a global scale and establish baseline expectations for how acoustic indices vary among biogeographic realms and biomes. Location Forests in Brunei, Ecuador, Gabon, Germany, Peru, Singapore, Sierra Leone and the USA, a dataset spanning two biomes and five out of six global biogeographic realms where forests occur. Time Period Two to five weeks of continuous audio data from each site collected between 2020 and 2024. Major Taxa Birds, amphibians, insects and mammals. Methods Stratifying data by time and frequency, we calculated four acoustic indices. Principal components analysis was used to compare the similarity of soundscapes across sites. Results Temperate and tropical forest soundscapes clustered separately in principal component analysis. Temperate forests had soundscapes which were uniformly loud during the day across all frequencies and were generally quiet at night. In contrast, all tropical locations had complex soundscapes during both day and night and had banding patterns suggestive of a high diversity of soniferous insects. These banding patterns were created by the unique soniferous community at each site, causing the ‘acoustic fingerprint’ of each site to be most similar to other sites in the same ecoregion and in the same biogeographic realm. The ‘acoustic fingerprints’ of temperate forest differentiated between ecoregions only when dawn was considered separately. Main Conclusions Our results stress the importance of using regional specific baseline data, as soundscapes are not necessarily comparable. Ecoacoustics is growing in popularity as an ecosystem monitoring tool, and understanding how forest soundscapes vary naturally across the globe can provide much needed context for studies that seek to understand factors that may disrupt or alter those soundscapes.

Net primary productivity but not its remote‐sensing proxies predict mammal diversity in Andean‐Amazonian rainforests - Kim L. Holzmann; Pedro Alonso‐Alonso; Yenny Correa‐Carmona; Andrea Pinos; Felipe Yon; Alejandro Lopera; Gunnar Brehm; Alexander Keller; Ingolf Steffan‐Dewenter; Marcell K. Peters (Ecology, 2025)
Tropical forests are disappearing, but we have a limited understanding of the factors driving species coexistence in mammal communities of old‐growth forest ecosystems. The total energy that is bound by plants is assumed to be a key factor determining mammalian species richness, but accurately measuring energy flows in complex ecosystems is difficult, and most studies therefore rely on remote‐sensing‐based surrogates of net primary productivity (NPP). We monitored mammal species richness across three seasons using camera traps on 26 study plots along a forested, elevational gradient from 245 to 3588 m above sea level in southeastern Peru for which a unique dataset on field‐measured NPP exists. Using linear‐regression models and path analysis, we disentangled the effects of climate and NPP on the diversity of mammals, testing the predictions of the more‐individuals hypothesis, stating that energy availability drives the number of individuals and, thus, the number of coexisting species. We compared detailed field measurements of NPP with remote‐sensing products (MODIS NPP and MODIS NDVI). Mammal species richness, abundance, and biomass decreased in a negative exponential pattern with elevation. Field‐measured data on NPP, which was largely driven by temperature, was a strong predictor of both abundance and species richness, while remotely sensed proxies for NPP failed to accurately predict mammal diversity. Our study underpins the importance of field‐based ecosystem data and emphasizes the role of high primary productivity for maintaining diverse mammal communities, which is a particularly pressing issue in light of recent anthropogenic impacts on the Amazonian forest system.

Early-life external exposome in children 2–5 years old in Colombia - Diana Marín; Xavier Basagaña; Ferney Amaya; Luis Miguel Aristizábal; Diego Alejandro Muñoz; Alan Domínguez; Francisco Molina; Carlos Daniel Ramos; Ricardo Morales-Betancourt; Roberto Hincapié; Laura Rodríguez-Villamizar; Yurley Rojas; et al. (Environmental Research, 2024)

Habitat type affects the diversity of dung beetle (Coleoptera: Scarabaeidae) assemblages in a neotropical mountainous region of Colombia - Renato Portela Salomão; Alejandro Lopera-Toro; Luz Astrid Pulido-Herrera; Jorge Armando Arias-Buriticá (International Journal of Tropical Insect Science, 2023)
Ecological communities of tropical regions respond to habitat configuration, being negatively affected by anthropogenic habitats. In the tropics, mountainous highland landscapes sustain ecological communities with contrasting responses to habitat transformation. This study assessed the effect of different habitats under different disturbance regimes on the dung beetle assemblage that inhabits a mountainous Andean landscape in Colombia. The habitat types surveyed were oak forest cores (low intervention), forest edges (medium intervention), and pastures (high intervention). A total of 3,810 dung beetles from ten species were collected. Dung beetle diversity was affected by habitat type, and forest cores and forest edges had higher diversity than pastures. Besides, each habitat type was characterized by a distinct dung beetle assemblage, with pastures showing the highest heterogeneity in the dung beetle assemblage. In conclusion, our study suggests that the dung beetles of a portion of Colombian Andean landscapes are sensitive to shifts of habitat quality. The higher dung beetle diversity in forested habitats indicates that pastures comprise limiting environments for their assemblages at this Andean region.

A morphological database for 606 Colombian bird species - Paola Montoya; Mailyn A. Gonzalez; Elkin A. Tenorio; Juan Pablo López‐Ordóñez; Alejandro Pinto Gómez; Diego Cueva; Aldemar A. Acevedo Rincón; Camilo Angarita Yanes; Héctor Manuel Arango Martínez; Orlando Armesto; Jefry S. Betancur; Angela Caguazango Castro; et al. (Ecology, 2018)
Colombia is the country with the highest bird diversity in the world. Despite active research in ornithology, compelling morphological information of most bird species is still sparse. However, morphological information is the baseline to understand how species respond to environmental variation and how ecosystems respond to species loss. As part of a national initiative, the Instituto Alexander von Humboldt in collaboration with 12 Colombian institutions and seven biological collections, measured up to 15 morphological traits of 9,892 individuals corresponding to 606 species: 3,492 from individuals captured in field and 6,400 from museum specimens. Species measured are mainly distributed in high Andean forest, páramo, and wetland ecosystems. Seven ornithological collections in Colombia and 18 páramo complexes throughout Colombia were visited from 2013 to 2015. The morphological traits involved measurements from bill (total and exposed culmen, bill width and depth), wing (length, area, wingspan, and the distance between longest primary and longest secondary), tail (length and shape), tarsus (length), hallux (length and claw hallux), and mass. The number of measured specimens per species was variable, ranging from 1 to 321 individuals with a median of four individuals per species. Overall, this database gathered morphological information for >30% of Colombian bird diversity. No copyright, proprietary, or cost restrictions apply; the data should be cited appropriately when used.

Understanding Trait‐Dependent Community Disassembly: Dung Beetles, Density Functions, and Forest Fragmentation - TROND H. LARSEN; ALEJANDRO LOPERA; ADRIAN FORSYTH (Conservation Biology, 2008)
Anthropogenic disturbances such as fragmentation are rapidly altering biodiversity, yet a lack of attention to species traits and abundance patterns has made the results of most studies difficult to generalize. We determined traits of extinction‐prone species and present a novel strategy for classifying species according to their population‐level response to a gradient of disturbance intensity. We examined the effects of forest fragmentation on dung beetle communities in an archipelago of 33 islands recently created by flooding in Venezuela. Species richness, density, and biomass all declined sharply with decreasing island area and increasing island isolation. Species richness was highly nested, indicating that local extinctions occurred nonrandomly. The most sensitive dung beetle species appeared to require at least 85 ha of forest, more than many large vertebrates. Extinction‐prone species were either large‐bodied, forest specialists, or uncommon. These explanatory variables were unrelated, suggesting at least 3 underlying causes of extirpation. Large species showed high wing loading (body mass/wing area) and a distinct flight strategy that may increase their area requirements. Although forest specificity made most species sensitive to fragmentation, a few persistent habitat generalists dispersed across the matrix. Density functions classified species into 4 response groups on the basis of their change in density with decreasing species richness. Sensitive and persistent species both declined with increasing fragmentation intensity, but persistent species occurred on more islands, which may be due to their higher baseline densities. Compensatory species increased in abundance following the initial loss of sensitive species, but rapidly declined with increasing fragmentation. Supertramp species (widespread habitat generalists) may be poor competitors but strong dispersers; their abundance peaked following the decline of the other 3 groups. Nevertheless, even the least sensitive species were extirpated or rare on the smallest and most isolated islands.